Health Care Provider Intervention and Utilization of Cessation Assistance in 12 Low- and Middle-Income Countries. Issue 2 (6th February 2018) - Owusu, Daniel; Wang, Ke-Sheng; Quinn, Megan; Aibangbee, Jocelyn; John, Rijo M; Mamudu, Hadii M
Abstract: Background and Aim: There is a need to improve utilization of cessation assistance in low- and middle-income countries (LMICs), and tobacco cessation research has been identified as priority in LMICs. This study evaluates the relationship between health care provider intervention and cessation assistance utilization in LMICs. Methods: Data from 13 967 participants (aged ≥15 years, 90.3% males) of the Global Adults Tobacco Survey conducted in 12 LMICs (74.3%–97.3% response rates) were analyzed with utilization of counseling/cessation clinic, WHO-recommended medications, and quitline as outcome variables. Health care provider intervention ("no intervention, " only "tobacco screening, " "quit advice") was the exposure variable. Weighted multiple logistic regression models were used to examine the relationship between each outcome variable and the exposure variable, adjusting for other covariates. Adjusted odds ratios (ORs) with 95% confidence intervals (CIs) are reported. Results: Approximately 52%, 8%, and 40% of participants received no intervention, only tobacco screening, and advice to quit, respectively. Overall, 0.4%, 1.9%, 3.0%, and 4.5% used quitline, WHO-recommended medications, counseling/cessation clinic, and any cessation assistance, respectively. Compared with no intervention, quit advice was associated with increased utilization of quitline (OR = 2.24, 95% CI = 1.2 to 4.4), WHO-recommended medications (OR = 1.67, 95% CI = 1.2 to 2.3), counseling/cessation clinic (OR = 4.41, 95% CI = 3.2 to 6.1), and any assistance (any of the three types) (OR = 2.80, 95% CI = 2.2 to 3.6). Conclusion: The findings of this study suggest that the incorporation of quit advice by health care providers in tobacco control programs and health care systems in LMICs could potentially improve utilization of cessation assistance to improve smoking cessation in LMICs. Implications: This first study of association between health care provider intervention and the utilization of cessation assistance in LMICs reports that there was a missed opportunity to provide quit advice to about 60% of smokers who visited a health care provider in the past year. The odds of utilization of counseling/cessation clinic, WHO-recommended medications, and quitline were significantly increased in participants who were advised to quit smoking. The results suggest that effective integration and implementation of advice to quit in tobacco control programs and the national health care systems may increase the use of cessation assistance to quit smoking.